Nursing the cardiac patient - Humphreys, Melanie; Wiley eBooks (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
Nursing the Cardiac Patient is a practical guide that addresses the management of cardiac patients across the spectrum of health care settings. It assists nurses to develop a complete understanding of the current evidence based practice and principles underlying the care and management of the cardiac patient. It combines theoretical and practical components of cardiac care in an accessible and user-friendly format, with case studies and practical examples throughout.
Acute coronary syndromes in perspective / Melanie Humphreys -- Reducing the risk : primary care initiatives / Melanie Humphreys and Brenda Cottam -- Assessment of the cardiovascular system / Jackie Yonker -- Diagnosing acute coronary syndrome / John McGowan -- Unstable angina / John McGowan -- Non-ST segment elevation infarction / Melanie Humphreys -- ST segment elevation infarction / Claire Rushton -- Therapeutic intervention in acute coronary syndromes / Jan Keenan -- Cardiothoracic care / Debbie Danitsch -- Arrhythmias and their management / Melanie Humphreys and Celia Warlow -- Emergency cardiac care / Melanie Humphreys and Lisa Cooper -- Chronic cardiac conditions and their management / Ian Jones and Ann Dormer -- Cardiac rehabilitation / Tim Grove -- Secondary prevention within the community / Tim Grove -- Ethical issues in cardiac care / Pauline Walsh and Fiona Foxall.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Heart -- Diseases -- Nursing -- Great Britain; Heart -- Diseases -- Patients -- Nursing -- Great Britain; HEALTH & FITNESS -- Diseases -- Heart; MEDICAL -- Cardiology; Cardiovascular Diseases -- nursing -- Great Britain; Nursing Care -- methods -- Great Britain; Electronic books